Religiosity and SDG-Aligned Public Relations: Constructing A Positive Organizational Image - Rizal Fahmi Muhammad; Ismi Dwi Astuti Nurhaeni; Andre Noevi Rahmanto (Profetika: Jurnal Studi Islam, 2025)
Objectives: The objective of the research is to analyze how religious values embedded in employee behavior and institutional communication strengthen both internal and external relational trust while supporting SDG 3 (Good Health and Well-Being), SDG 4 (Quality Education), and SDG 16 (Peace, Justice, and Strong Institutions). Theoretical framework: The theoretical framework is grounded in the concepts of religious work ethics, impression management theory, and strategic communication within an SDG-oriented governance model. Literature review: The literature review highlights existing scholarship on the role of religiosity in organizational behavior, ethics-based PR strategies, and the global shift toward value-driven institutional communication aligned with international development frameworks. Methods: Methodologically, this study employs a qualitative descriptive design using primary data obtained through interviews, observation, and institutional documentation. The descriptive approach enables a comprehensive portrayal of employee religious practices such as routine religious studies, collective prayers, daily spiritual reflection, and capacity-building programs in Qur’an literacy and ritual correctness, which serve as internal PR mechanisms strengthening workplace discipline, empathy, and service ethics. Results: The findings reveal that religiosity functions as an internal cultural driver that elevates service quality, enhances patient or client satisfaction, and fosters a perception of organizational integrity. Externally, community engagement efforts such as outreach visits, collaboration with local leaders, public health education, and free health screenings reinforce SDG-aligned social responsibility, expanding public trust and institutional legitimacy. Crisis-handling strategies rooted in ethical reflection, problem clarification, and transparent communication further strengthen the organization’s positive image. Implications: The implications indicate that integrating religiosity with SDG-based PR frameworks can create synergistic value, fostering inclusive, ethical, and sustainable reputation management. Novelty: The novelty of this study lies in demonstrating how religiosity is not merely a personal moral attribute but a strategic institutional asset that reinforces SDG-compliant communication, enhances organizational credibility, and strengthens long-term stakeholder relations.